Construction of Phosphomannose Isomerase (PMI) Transformation Vectors and Evaluation of the Effectiveness of Vectors in Tobacco (Nicotiana tabacum L) - Bahariah, B.; Parveez, G.K.A.; Masani, M.Y.A.; Khalid, N. (2012)
Phosphomannose isomerase (pmi) gene isolated from Escherichia coli allows transgenic plants carrying it to convert mannose-6- phosphate (from mannose), a carbon source that could not be naturally utilized by plants into fructose-6-phosphate which can be utilized by plants as a carbon source. This conversion ability provides energy source to allow the transformed cells to survive on the medium containing mannose. In this study, four transformation vectors carrying the pmi gene alone or in combination with the beta-glucuronidase (gusA) gene were constructed and driven by either the maize ubiquitin (Ubi1) or the cauliflower mosaic virus (CaMV35S) promoter. Restriction digestion, PCR amplification and sequencing were carried out to ensure sequence integrity and orientation. Tobacco was used as a model system to study the effectiveness of the constructs and selection system. PMI11G and pMI3G, which carry gusA gene, were used to study the gene transient expression in tobacco. PMI3 construct, which only carries the pmi gene driven by CaMV35S promoter, was stably transformed into tobacco using biolistics after selection on 30 g 1(-1) mannose without sucrose. Transgenic plants were verified using PCR analysis.